Answer:
[tex] a_n = 31 - 3n\\\\
a_{30}= 59[/tex]
Step-by-step explanation:
Given Arithmetic sequence is:
28, 25, 22, 19, ...
a = 28, d = 25 - 28 = - 3,
nth term of an Arithmetic sequence is given as:
[tex] a_n = a + (n - 1) d\\[/tex]
Plugging a = 28 & d = - 3 in the above equation, we find:
[tex] a_n = 28 + (n - 1) (-3)\\\\
a_n = 28 - 3n +3\\\\
\huge\purple {\boxed {a_n = 31 - 3n}} \\(This \:is \:the \:required \:equation) \\\\
Plug \: n = 30, \: we \: find:\\\\
a_{30}= 31 - 3 \times 30\\\\
a_{30}= 31 - 90\\\\
\huge\orange {\boxed {a_{30}= 59}} \\\\
[/tex]